International Financial Statistics, April 2016. (International Financial Statistics; International Financial Statistics ;, 2016)
This April 2016 issue of International Financial Statistics (IFS) is a standard source of statistics on all aspects of international and domestic finance. The IMF publishes calculated effective exchange rates data only for countries that have given their approval. The IMF cannot allocate SDRs to itself but receives them from members through various financial transactions and operations. Entities authorized to conduct transactions in SDRs are the IMF itself, participants in the SDR Department, and other 'prescribed holders.' The IMF quota increase under the Fourteenth General Review of Quotas became effective recently. The details regarding the associated change can be found in the IMF Press Release No. 16/25, dated January 27, 2016. The effect of quota payments is reflected in the following Fund Accounts for those members that have made their quota payments: Quota, Reserve Tranche Position, Fund Holdings of Currency, SDR Holdings. It is also reflected in the international liquidity and central bank data.